PENGEMBANGAN MEDIA PEMBELAJARAN IPAS MENGGUNAKAN PLATFORM WORDWALL BERBASIS MODEL PEMBELAJARAN RADEC DI KELAS V SEKOLAH DASAR - Novela, Dina; Erita, Yeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research was motivated by the limited use of digital learning media in schools. The research aims to develop a valid, practical and effective IPS learning media using the Wordwall Platform based on the RADEC learning model in grade V of elementary school. The research uses a type of development research with a plomp model. The stages are: (1) initial investigation phase, (2) design phase, (3) realization phase, (4) test, revision and evaluation phase, and (5) implementation phase. Learning media are designed then tested for feasibility through validity tests, followed by practicality tests by filling out teacher and student response questionnaires. Then the effectiveness test is carried out to determine the influence or impact of learning outcomes using learning media. The validity of learning media is categorized as very valid with an average validator assessment of 90%. Practicality in the trial school is categorized as very practical with a percentage of teacher responses of 95% and student responses of 94.6%. While practicality in the research school for teacher responses is 92.5% and student responses of 94.7%. The effectiveness of learning media in the trial school is categorized as very effective with a percentage of 90%, while the effectiveness in the research school is 89.8%. Thus, the development of science learning media using the Wordwall Platform based on the RADEC learning model in grade V of elementary school has been valid, practical and effective for use in learning.